2021
DOI: 10.1002/ajmg.a.62346
|View full text |Cite
|
Sign up to set email alerts
|

Central 22q11.2 deletion (LCR22 B‐D) in a fetus with severe fetal growth restriction and a mother with severe systemic lupus erythematosus: Further evidence of CRKL haploinsufficiency in the pathogenesis of 22q11.2 deletion syndrome

Abstract: 22q11.2 deletion syndrome (22q11.2 DS, MIM #188400) is the most common chromosomal microdeletion with an incidence of 1 in 4000 live births. 22q11.2 DS patients present with varying penetrance and a broad phenotypic spectrum including dysmorphic features, congenital heart defects, hypoplastic thymus and T‐cell deficiency, and hypocalcemia. The typical deletion spans 3 Mb between 4 large blocks of repetitive DNA, known as low copy repeats (LCRs), on chromosome 22 (LCR22) A and D. This deletion is found in ~85% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The 22q11.2DS is usually diagnosed by FISH using commercial probes, including TUPLE1 (flanked by LCR A-B of 22q11.2 deletion). Another limitation of the study is that this probe has a detection yield of 85% for classic 2.55 Mb deletion spanning LCR A-D but only 5% and 2% of the atypical deletions spanning LCR A-B and A-C, respectively 4,13,14,16 . Therefore, it is possible that our interphase FISH studies missed some cases with deletions without the involvement of the A-B region.…”
Section: Discussionmentioning
confidence: 99%
“…The 22q11.2DS is usually diagnosed by FISH using commercial probes, including TUPLE1 (flanked by LCR A-B of 22q11.2 deletion). Another limitation of the study is that this probe has a detection yield of 85% for classic 2.55 Mb deletion spanning LCR A-D but only 5% and 2% of the atypical deletions spanning LCR A-B and A-C, respectively 4,13,14,16 . Therefore, it is possible that our interphase FISH studies missed some cases with deletions without the involvement of the A-B region.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 15q24 Microdeletion Syndrome (#613,406) and 8q21.11 Microdeletion Syndrome (#614,230) were rarely characterized by FGR 25 . As for 22q11.21 microdeletion, which is responsible for DiGeorge Syndrome or Velocardiofacial Syndrome, FGR was frequently reported in FGR with structural malformations 12 , 26 28 . In one case (case 1) presenting FGR and ventricular septal defect (VSD), a 2.6 Mb deletion was detected in the region of 3q26.33-3q27.2, involving 30 OMIM genes.…”
Section: Discussionmentioning
confidence: 99%
“…When neurons are edema, degeneration, and necrosis, NSE can be released into cerebrospinal fluid and blood. Many scholars have confirmed that the level of serum NSE is significantly increased in cerebrovascular disease, neonatal hypoxic-ischemic encephalopathy, epilepsy, cardiogenic hypoxic-ischemic brain injury, brain trauma, and other diseases [ 26 ]. Among the data of our study, one patient with SLE had no neuropsychiatric symptoms and signs on admission, but his serum NSE increased significantly, and she had a major seizure 2 days later.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of its hidden performance and no specific and sensitive diagnostic methods, it is often ignored in clinical work, so it cannot be treated timely. The change of serum NSE level can early and specifically reflect the pathological changes of CNS during SLE, so it may be employed as a sensitive index to judge the existence of lupus encephalopathy in the early stage so as to provide a theoretical basis for the prevention and treatment of lupus encephalopathy [ 26 ]. At present, the detailed mechanism of the increase of serum NSE in SLE is not well understood, but it is believed to be mainly related to the following: (1) a variety of autoantibodies (antinuclear antibodies and anti-brain cell antibodies) combine with corresponding antigens to form immune complexes with the complements, which deposit on the blood vessel wall to cause cerebral vasculitis; (2) some small emboli form heart valve vegetations; (3) anticardiolipin antibodies directly act on the phospholipid components of vascular endothelial cells and platelets, leading to small thrombosis, causing microinfarction, hemorrhage, edema and brain tissue softening, and other factors, which lead to CNS lesions in patients with SLE, resulting in the increase of serum NSE levels, but the course and prognosis of NSE and SLE need to be further studied [ 27 ].…”
Section: Discussionmentioning
confidence: 99%